Organizational performance assessment in hotel industry: a systematic review - Arenhart, Rodrigo Schons; Souza, Adriano Mendonça; Zanini, Roselaine Ruviaro (Revista Gestão da Produção Operações e Sistemas, 2023)
Purpose: this study aims to analyze how the hotel industry uses quantitative data to assess its organizational performance. Design/Methodology/Approach: a systematic review (SR), with a descriptive analysis and critical information, was carried out to develop a holistic view of the theme and offer guidance for future research. Findings: the review presented information on the topic, covering studies in environmental efficiency, financial performance, social analysis, and the global details on performance in the hotel industry. The paper shows main research topics/indicators on hotel performance assessment and proposes a more comprehensive path for research. Research, Practical & Social Implications: the findings contribute to the understanding of managers of hotels with solutions found in relevant scientific studies and with researchers identifying research gaps in main areas. Originality/Value: the review demonstrates the potential for further research in three main areas (economic, environmental, and social). Besides this, an important and promising area of research is shown: to understand the role of each potential component in the global performance of hotels. Keywords: Hotels; Organizational Performance; Systematic Review.